The Impact of Medically Indicated and Spontaneous Preterm Birth among Hypertensive Women - Kase, Benjamin A.; Carreno, Carlos A.; Blackwell, Sean C.; Sibai, Baha M. (American Journal of Perinatology, 2013)
Objective To (1) describe the frequency of spontaneous preterm birth (SPTB) and medically indicated preterm birth (PTB) among women with chronic hypertension (CHTN) and (2) to evaluate differences in neonatal outcomes according to SPTB or medically indicated PTB.Study Design Retrospective analysis of a previously conducted multicenter randomized trial. Deliveries were categorized as SPTB or medically indicated and stratified by gestational ages (<37 weeks, 34 to 366/7 weeks, 30 to 336/7 weeks, < 30 weeks). Rates of neonatal intensive care unit admission, composite respiratory morbidity, perinatal mortality, and small for gestational age (SGA) were evaluated.Results Of 765 women, 32.2% (n = 246) delivered at < 37 weeks, of which 10.5% (n = 80) were SPTB and 21.6% (n = 166) were medically indicated. Fifty-nine percent of PTBs occurred in the late preterm period (n = 146). SGA was significantly more frequent among those with medically indicated PTB at < 30 weeks (p = 0.03). There were no other differences in adverse neonatal outcomes between medically indicated versus SPTB at any gestational age (p > 0.05).Conclusion Nearly one-third of women with CHTN delivered preterm. The majority of PTBs were medically indicated and late preterm, but approximately one-third were due to SPTB.
Keywords: chronic hypertension; preterm birth; respiratory morbidity; stillbirth